International monetary system: Past, present and future (reseña) - Urbina Padilla, Dante Abelardo (2016)
International Monetary System: Past, Present and Future is an extraordinary book in which, through numerous scientific articles (papers) that were complied and edited by Dr. Debesh Bhowmik, the important issue of the international monetary system is approached from a broad perspective in its economic, historical, technological, regional and even political aspect in relation to relevant topics such as economic crisis, development, international trade and theoretical discussions about the orthodox and heterodox approach.